A conceptual framework for the cognitive enterprise: pillars, maturity, value drivers. Issue 4 (3rd April 2022) - Elia, Gianluca; Margherita, Alessandro
ABSTRACT: Digital transformation is driving the emergence of a new breed of organisations able to scale quickly, innovate throughout their processes, and lead industries and markets. In particular, the increasing adoption of cognitive technologies, like artificial intelligence, advanced analytics, high-performing computing and cyber-physical systems, allow organisations to create new value based on increased reactivity and resilience, situational awareness, agility and operational excellence. Although the idea of cognitive enterprise is rapidly emerging in the practitioner discussion, a theoretical framing of the concept is still not present in literature. We conduct a systematic review of extant contributions and we extract elements related to two key dimensions represented by the cognitive technological infrastructure (i.e. technologies and data) and the cognitive organizational architecture (i.e. processes and capabilities). We use the outcomes of the review work to define: (a) the pillars of the cognitive enterprise; (b) a framework of cognitive maturity stages; and (c) the enhanced value creation capabilities of the cognitive enterprise. The article provides a literature-derived definition of the cognitive enterprise and guidelines to support managers in the cognitive transformation of their organisations.